Comparison of self-regulation strategies in elite basketball players based on personality types - Shandi, M. P.; Ardekani, Z. P.; Mehri, S. (American Journal of Sports Science, 2016)
Introduction: Nowadays, identification of factors related to success of athletes is considered as one of the important issues in psychology of sport. Self-regulation is one of these factors investigated recently. The aim of this study is to compare self-regulation strategies of Iranian basketball players based on their personality types. Method: subjects of this study were male basketball players of Iranian super league in 2013-2014, which 118 of them were selected as sample of study, based on Morgan sample size table. Miller and Brown`s Self-Regulation Questionnaire and Eysenck personality were used in this study. Since the number of introverts was low, they were excluded in the present study. In addition, sample of study was divided into two groups of stable extroverts and unstable extroverts, based on Eysenck personality. Results: results indicated that there was significant difference between two groups. Results also showed that each of these groups use various strategies to self-regulation. Conclusion: considering personality types, individuals can use various strategies for self-regulation that this issue can play role in achieving their goals and successes.